2001
DOI: 10.2223/jped.185
|View full text |Cite
|
Sign up to set email alerts
|

Antistreptolysin O titer profile in acute rheumatic fever diagnosis

Abstract: ResumoObjetivo: estabelecer o perfil dos títulos de ASO, mediante o diagnóstico diferencial da FRA com outras afecções que também cursam com níveis elevados de ASO.Métodos: foram estudados 78 casos de FRA na apresentação e seguimento, 22 de coréia isolada, 45 de infecções orofaringeanas recorrentes (IOR) e 23 de artrites idiopáticas juvenis (AIJ), com início ou reativação recente. A determinação seqüencial de ASO (UI/ml) foi realizada por ensaio nefelométrico automatizado (Behring ® -Germany) nos períodos de 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
2
12
0
4
Order By: Relevance
“…8 A study in Portugal investigated 78 children with Acute Rheumatic Fever at admission and follow up, also 22 children with Chorea, 45 children with recurrent tonsillitis and 23 with Juvenile idiopathic arthritis were also similarly followed up and the researchers concluded that a reappraisal of the ASO titers in Acute Rheumatic Fever indicates a significant response in the acute phase and helps to distinguish it from other diseases with high ASO titers. 9 There is no unanimity or consensus among clinicians about the absolute usefulness of ASO titer and different studies have provided contrary results and conclusions. A study in Poland however concluded that an increased serum antibody titers to streptolysin O is usually indicative of recent streptococcal infection and not active rheumatic fever.…”
Section: Discussionmentioning
confidence: 99%
“…8 A study in Portugal investigated 78 children with Acute Rheumatic Fever at admission and follow up, also 22 children with Chorea, 45 children with recurrent tonsillitis and 23 with Juvenile idiopathic arthritis were also similarly followed up and the researchers concluded that a reappraisal of the ASO titers in Acute Rheumatic Fever indicates a significant response in the acute phase and helps to distinguish it from other diseases with high ASO titers. 9 There is no unanimity or consensus among clinicians about the absolute usefulness of ASO titer and different studies have provided contrary results and conclusions. A study in Poland however concluded that an increased serum antibody titers to streptolysin O is usually indicative of recent streptococcal infection and not active rheumatic fever.…”
Section: Discussionmentioning
confidence: 99%
“…Antistreptolysin-O rising titres in RF cases from our unit were previously examined, stressing the importance of serial determination over the fi rst two months. 25 The tests of acute phase response indicated high erythrocyte sedimentation rate in 58.3% and C-reactive protein in 45.9%, and again a wide variation is observed in the published series. [11][12][13][14][15][16][17][18]24 It is possible that different laboratory techniques might have infl uenced these results in the same way for antistreptolysin-O, but it was not possible to reach a conclusion, due to the retrospective approach.…”
mentioning
confidence: 86%
“…Recomenda-se a realização de duas dosagens de ASLO com intervalo de 15 dias (IB). Tem sido observado que aproximadamente 20% dos pacientes com FR não cursam com elevação da ASLO 28 . Recomenda-se a utilização dos limitespadrão de cada laboratório para a análise dos resultados.…”
Section: A Resposta Imune Na Doença Reumáticaunclassified